RESPON TURKI TERHADAP PELANGGARAN HAM MINORITAS MUSLIM UIGHUR YANG DILAKUKAN OLEH PEMERINTAH TIONGKOK 2009-2010 - Siti Nida Laylia; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The Uyghurs are an ethnic group living in the western part of China. The presence of different ethnic Uighurs with ethnic Chinese majority and Uighur ethnic refusal to become part of China resulted in pressure from the Chinese Government. The existence of Chinese government pressure is causing resistance and ethnic Uighur separatism.The Chinese government's actions sparked protests and demonstrations from ethnic Uighurs, leading to the biggest unrest that occurred on July 5, 2009. Turkey, which has primordialism ties to Uighurs from historical, cultural, linguistic and religious affiliations, reacted strongly through the protests of Prime Minister Erdogan and Turkish public through demonstrations and mass media. But in September 2010, the two countries conducted joint military exercises on Turkish invitations and were followed by the highest-level visits by the two countries' elites, as well as ties between the two countries, with cooperation in various fields initiated by Turkey and China.Using a conceptual framework of motivations that encourage a country to react to ethnic conflicts involving its ethnic ties, the study concludes that there are factors other than affective factors that influence Turkey's attitude toward the Uighurs who inhabit the Xinjiang region and Turkish relations and its relationship with China .Keywords : ethnicity, Turkey, Uyghur, China, policy, foreign policy